Geoscience Medallist 1. Understanding the Holocene Closed-Basin Phases (Lowstands) of the Laurentian Great Lakes and Their Significance - Lewis, C.F.M. (Geoscience Canada, 2016)
The Laurentian Great Lakes are a chain of five large water bodies and connecting rivers that constitute the headwaters of the St. Lawrence River. Collectively they form one of the largest reservoirs of surface freshwater on the planet with an aggregate volume of >22,000 km3. Early interpretations of the postglacial lake history implicitly assumed that the Great Lakes always overflowed their outlets. A study of Lake Winnipeg which concluded that lack of water in a dry climate had dried that lake for millennia led to re-evaluation of the Great Lakes water-level history. Using the empirical information of glacioisostatic rebound derived from 14C-dated and uptilted Great Lake paleo-shorelines, a method of computation was developed to test the paradigm of continuous lake overflow. The method evaluated site and outlet uplift independently, and low-level indicators such as submerged tree stumps rooted beneath the present Great Lakes were found to be lower than the lowest possible corresponding basin outlet. Results confirmed the low-level, closed-basin hydrological status of the early Great Lakes. This status is consistent with paleoclimatic inferences of aridity during the early Holocene before establishment of the present patterns of atmospheric circulation which now bring adequate precipitation to maintain the overflowing lakes. In a sense, the early to middle Holocene phase of dry climate and low water levels is a natural experiment to illustrate the sensitivity of the Great Lakes to climate change in this era of global warming, should their climate shift to one much drier than present, or future major diversions of their waters be permitted.